Modelling written communication a new systems approach to modelling in the social sciences - Pratt, Deirdre; SpringerLink (Online service). (Dordrecht Springer, 2011)
This book offers an alternative view to current postmodern approaches to composition. It takes a critical realist stance to arrive at the 'essence' of written communication with the aim of informing a practical application: a computerised writing tutor. Following Robert Franck's seminal work on modelling, a theoretical model of writing was first formulated, consisting of an architecture of functions which constitute the prerequisites for effective communication. Next, an applied model - a composing algorithm with an input option - was developed, showing composing to be a systemic social process with intra- and extra-systemic variation. The algorithm provided the design template for a writing tutor program which models for the learner both the systemic and the socially situated nature of writing. This book establishes composing as a communicative interaction, and shows the essential dynamism of writing, while offering an exemplar of a systems approach to modelling in the social sciences
Preface Glossary Introduction Chapter 1: Review of Composition Software Chapter 2: Critical Realism Chapter 3: The Modelling Process Chapter 4: The User's Model of Composing Chapter 5: Testing out the User's Model Chapter 6: The Theoretical Model of Composing Chapter 7: The Explanatory Force of the Models Chapter 8: The Writing Tutor Program Conclusion Index Bibiography
Includes bibliographical references (pages 213-222) and index
Electronic reproduction
Keywords: Written communication -- Social aspects